Reduced Sleep-Like Quiescence in Both Hyperactive and Hypoactive Mutants of the Galphaq Gene egl-30 during lethargus in Caenorhabditis elegans - Schwarz, Juliane (Public Library of Science, 2013)

(untitled)
Sleep-like states are characterized by massively reduced behavioral activity. Little is known about genetic control of sleep-like behavior. It is also not clear how general activity levels during wake-like behavior influence activity levels during sleep-like behavior. Mutations that increase wake-like activity are generally believed to also increase activity during sleep-like behavior and mutations that decrease wake-like activity are believed to have decreased activity during sleep-like behavior. We studied sleep-like behavior during lethargus in larvae of Caenorhabditis elegans. We looked through a small set of known mutants with altered activity levels. As expected, mutants with increased activity levels typically showed less sleep-like behavior. Among these hyperactive mutants was a gain-of-function mutant of the conserved heterotrimeric G protein subunit Galphaq gene egl-30. We found, however, that an unusual semidominant hypoactive mutant of egl-30 also had reduced sleep-like behavior. While movement was severely reduced and impaired in the semidominant egl-30 mutant, sleep-like behavior was severely reduced: the semidominant egl-30 mutant lacked prolonged periods of complete immobility, reduced spontaneous neural activity less, and reduced responsiveness to stimulation less. egl-30 is a well-known regulator of behavior. Our results suggest that egl-30 controls not only general activity levels, but also differences between wake-like and sleep-like behavior.